Kirby, Biggers, and Ash: Do Any Constitutional Safeguards Remain Against the Danger of Convicting the Innocent? - Grano, Joseph D. (1974)
Even recognizing the danger of misidentification, procedural safeguards, especially constitutional ones, are not readily apparent. Some judges, such as Justice Stewart, find less need for counsel at photographic displays than at lineups; others find an equivalent or even greater need for counsel. Some judges, in approving on-the-scene identifications without counsel, find a guarantee of accuracy in the short interval between the crime and the identification; other judges decry such procedures and find them inherently suggestive. The problem stems directly from the lack of scientific knowledge and inquiry. Therefore, in analyzing the recent identification cases, this Article will draw upon experimental results that seriously challenge present methods; more importantly, it will seek to define those areas where further scientific inquiry is needed to replace judicial speculation